Model Pembelajaran POE Termodifikasi: Pengaruhnya terhadap Motivasi Belajar IPA dan Keterampilan Berpikir Kritis Siswa - Fatimah Millenia Fauziah; Anak Agung Istri Agung Rai Sudiatmika; I Wayan Suja (Jurnal Penelitian Pendidikan IPA, 2023)
This research aims to describe and explain simultaneously whether there are differences in science learning motivation and critical thinking skills of students who learn using different learning models. The experimental class is with modified POE, while the control class is with a conventional learning model. This type of research is a quasi-experimental research design with a nonequivalent pretest-posttest control group design. The data obtained were analyzed descriptively and the hypothesis was tested using MANCOVA. The research results showed that simultaneously there were significant differences in science learning motivation and students' critical thinking skills between the experimental and control classes in terms of the results of the analysis of the students' achievements. The modified POE learning model is better at increasing students' science learning motivation and thinking skills compared to 5M learning.